Mechanical effects of sodium pentaborate pentahydrate and sodium pentaborate anhydrate additives in polypropylene - Şahin, Burhan; Atik, Enver (İdris Karagöz, 2025)
This research examines the effect of micro size sodium pentaborate pentahydrate and anhydrate forms on the physicochemical and mechanical properties of filled polypropylene (isotactic homopolimer – Borealis HE125MO) composite matrices. The Sodium pentaborate pentahydrate and anhydrite dried 105°C 1 hour and mixed with micro compounder with polypropylene (with different proportions) and produced test samples with injection molding method. Mechanical properties were measured (tensile strength, modulus of elasticity, ultimate strength, tensile at yield (at room temperature)) along with hardness (charpy impact) test. Increasing filler content lead to an increase mechanical strength of the composite material depends on the percentage quantity of mixture proportion. The observed increase in tensile strength is %4,2 with %1 sodium pentaborate pentahydrate additive. The modulus of elasticity increases with additive quantity and the ultimate strength and strain at yield effected parallel with tensile strength change. With high proportion (%5-%10) of filler content, the mechanical properties decreased but increased the hardness. To understand the physicochemical effects, FTIR test applied on samples and O-H bonds effects and C-C bonds change observed. According to Infrared spectroscopy, the polypropylene had changed 1,56% with sodium pentaborate pentahydrate additive and 2,86% with %1,5 additive of sodium pentaborate anhydrite form. The fingerprint region alterations at FTIR tests and water effect observed. The molecular bonding effects of sodium pentaborate with chain of isotactic homopolimer examined. The nucleating effect of sodium pentaborate in polypropylene is viewed with SEM test. In microstructure, positioning effects of sodium pentaborate particles in chain/fiber structure of polypropylene observed and associated with mechanical properties and physicochemical impacts.

Bu çalışma, mikro boyutlu sodyum penta boratın, hem pentahidrat hem de anhidrat formlarının, dolgu maddesi içeren polipropilen (izotaktik homopolimer – Borealis HE125MO) kompozitlerinin fizikokimyasal ve mekanik özelliklerini nasıl etkilediğini incelemektedir. Sodyum penta borat formları, 105°C'de bir saat süreyle kurutulmuş ve çeşitli oranlarda polipropilen ile mikro bileştirici kullanılarak karıştırılmış, örnekler enjeksiyon kalıplama yöntemiyle üretilmiştir. Çekme dayanımı, elastik modül, nihai dayanım ve akma çekme dayanımı (oda sıcaklığında) gibi mekanik özellikler değerlendirilmiş, ayrıca Charpy darbe testi ile sertlik ölçülmüştür. Artan dolgu maddesi içeriği, kompozitin mekanik dayanımını artırmış ve %1 sodyum penta borat pentahidrat ile çekme dayanımında dikkate değer bir %4.2 artış gözlemlenmiştir. Elastik modül de daha fazla katkı maddesi ile artarken, nihai dayanım ve akma deformasyonu çekme dayanımındaki değişimlerle farklılık göstermiştir. Ancak, daha yüksek dolgu seviyelerinde (%5-10) mekanik özellikler düşmüş, buna karşın sertlik artmıştır. FTIR analizi, O-H ve C-C bağlarındaki değişiklikleri göstermiş, sodyum penta borat pentahidrat ile polipropilenin %1.56 oranında değişim ve %1.5 sodyum penta borat anhidrat ile %2.86 oranında değişim yaşandığını ortaya koymuştur. FTIR sırasında parmak izi bölgesindeki değişiklikler ve suyun etkileri gözlemlenmiştir. Sodyum penta borat ile izotaktik homopolimer arasındaki moleküler etkileşimler analiz edilmiş ve SEM analizi, sodyum penta boratın polipropilen içindeki nucleating etkisini ortaya koyarak, polimerin mikro yapısı içindeki konumunu göstermiştir.
Polipropilende Sodyum Pentaborat Pentahidrat ve anhidrit formlarının mekanik etkileri
Keywords: Material Design and Behaviors; Malzeme Tasarım ve Davranışları